2023
DOI: 10.3390/c9020040
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic, Iron, and Manganese Adsorption in Single and Trinary Heavy Metal Solution Systems by Bamboo-Derived Biochars

Abstract: Currently, heavy metal-contaminated groundwater is an environmental concern. This study investigated the use of bamboo biochar, chitosan-impregnated biochar, and iron-impregnated biochar for arsenic, iron, and manganese removal from groundwater. Isotherms of arsenic, iron, and manganese adsorption by bamboo derived biochar were compared with those of commercial activated carbon in simulated groundwater composed of single and trinary heavy metal solutions. The binding of heavy metals by virgin and loaded bamboo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Mangrove, bamboo, and palm shell were collected from local communities in Thailand. Biochars derived from mangrove (MB) and bamboo (BB) were produced in a traditional brick kiln under slow pyrolysis at 500 ± 100 °C (adopted from Be et al 29 and Pinisakul et al 30 ). Palm-shell-derived biochar (PSB) was produced in an iron bucket under slow pyrolysis at 400 ± 100 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Mangrove, bamboo, and palm shell were collected from local communities in Thailand. Biochars derived from mangrove (MB) and bamboo (BB) were produced in a traditional brick kiln under slow pyrolysis at 500 ± 100 °C (adopted from Be et al 29 and Pinisakul et al 30 ). Palm-shell-derived biochar (PSB) was produced in an iron bucket under slow pyrolysis at 400 ± 100 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The BB-C2 sample has a less rough or cracked outside surface, as seen in Figures 11(a) and 11(a-1), due to less fluctuation of temperature while slow low heating rates occurred (Ong et al, 2021;Zhang et al, 2020) during the pyrolysis process of the stove, and heat is likely to transfer through the longitudinal direction rather than in the radius direction of bamboo wood chunks (Kalderis et al, 2023;Pinisakul et al, 2023). However, increasing pyrolysis temperature results in improved total surface and pore volumes of biochar (Binh et al, 2022;Hettithanthri et al, 2023;Faraji et al, 2023), but a thinner wall of the pore was found due to the decomposition of hemicellulose, cellulose, and lignin with increased temperature (Figures 11b and 11b-1).…”
Section: The Surface Morphologies and Chemical Compositionmentioning
confidence: 99%
“…With the current rise in industrial activity, there is an accompanying increase in the discharge of industrial effluents containing various unknown inorganic contaminants. Among these contaminants are hazardous heavy metals, including copper (Cu) [ 1 ], mercury (Hg) [ 2 ], lead (Pb) [ 3 ], cadmium (Cd) [ 4 ], cobalt (Co) [ 5 ], arsenic (As) [ 6 ], and iron (Fe) [ 7 ]. Even at low concentrations, the heavy metals cause health risks when they accumulate in the human body, leading to issues such as anorexia, hepatitis, nephritis syndrome, kidney damage, insomnia, and cancer [ 8 ].…”
Section: Introductionmentioning
confidence: 99%